Ditching the Driving: A Cross-Sectional Study on the Determinants of Remote Work From Home for Sign Language Interpreters - Roman, Gretchen; Samar, Vincent; Ossip, Deborah; McKee, Michael; Barnett, Steven; Yousefi-Nooraie, Reza (Frontiers in Health Services, 2022)
Background The coronavirus disease 2019 (COVID-19) pandemic dramatically impacted the working conditions for sign language interpreters, shifting the provision of interpreting services from onsite to remote. The goal of this cross-sectional study was to examine the perceptions of determinants of remote interpreting implementation from home by sign language interpreters during the pandemic. We hypothesized that interpreters working across the primary settings of staff (agency, government, business, or hospital employees), educational (K-12 or postsecondary), community/freelance (independent contractor), video remote (the two-way connection between onsite participants and remote interpreter), and video relay (three-way telecommunication) would present with differing experiences of the implementation process. Methods The Determinants of Implementation Behavior Questionnaire was adapted for sign language interpreters (DIBQ-SLI) and administered to certified interpreters working remotely at least 10 h per week. The DIBQ-SLI included eight constructs (knowledge, skills, self-efficacy, perceived behavioral control, innovation characteristics, organizational resources and support, innovation strategies, and social support) and 30 items. Parametric statistics assessed differences in interpreters' perceptions across settings. Principal component analysis was conducted for data reduction and affirmation of the most critical constructs and items. Results One hundred and six interpreters (37 video relay, 27 video remote, 18 educational, 11 community/freelance, 11 staff interpreters, and two from “other” settings) completed the DIBQ-SLI. The video relay and staff interpreters consistently demonstrated the most favorable and the educational interpreters demonstrated the least favorable perceptions. Of the total variance, 58.8% of interpreters' perceptions was explained by organizational (41%), individual (10.7%), and social (7.1%) dimensions. There were significant differences across settings for the organizational and individual principal components; however, no differences were detected for the social principal component. Conclusions An administrative infrastructure devoted to ensuring that interpreters receive sufficient managerial support, training, materials and resources, experience with remote interpreting before having to commit, and insights based on the results of their remote work (organizational principal component) may be necessary for improving perceptions. Remote interpreting is expected to continue after the pandemic ends; thus, settings with the least favorable ratings across behavior constructs may borrow strategies from settings with the most favorable ratings to help promote perceptions of the contextual determinants of future remote interpreting implementation.